Percepções do desenho em um suporte ready-made - Santos, Greicy Kelly Teixeira dos (Revista do Colóquio, 2023)
This article presents considerations about the process of creating an object, named Observatório do Desenho, carried out in 2022. This work traces very close relationships between an object as a matrix support and operations that articulate the realization of a three-dimensional drawing. In this way, the text seeks to build reflections on questions about the object in its materiality and its possibility of being perceived as a drawing, considering some elements that constitute the relationship between plane versus line, as well as its implications with the ready-made object.